THE RELATIONSHIP OF FATHER'S INVOLVEMENT IN PARENTING AND INTERPERSONAL INTELLIGENCE OF YOUNG CHILDREN - Merta Verani; Abdus Somad; Jhoni Warmansyah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
The involvement of fathers in parenting is an interesting discussion today. Many research show positive impacts of fathers' interactions in parenting on child development. The reality in Jakarta is that fathers work full time all day, and many fathers still think that child management is the mother's duty. This study aimed to see how the relationship between the father's interaction in parenting and the child's interpersonal intelligence. This study used a sample of 115 fathers, and children were collected using a simple random sampling technique. The research method used is correlational. The instrument was a questionnaire compiled independently and distributed to the father to measure the father's interactions in parenting in the form of a Likert scale, interpersonal intelligence measured through a multiple intelligence instrument (Jamaris, 2018). Based on data analysis using Pearson's current product trials, the researcher found that trust (rxy) was 0, 509 with p = 0.000 (p <0.001). Thus, it can be stated that the higher the father is involved in parenting, the better the level of development of the child's interpersonal intelligence. The role of fathers in parenting is significant in child development, especially in developing multiple intelligence possessed by children.